HIGHER VOCATIONAL STUDENTS’ PERCEPTIONS ON THE USE OF CANVAS INSTRUCTURE IN BLENDED FLIPPED-INSTRUCTED ESP CLASSES - Putu Tika Virginiya (Yavana Bhasha : Journal of English Language Education, 2023)
During the epidemic era and because of COVID-19, especially when online learning was required and the only means to deliver instruction, learning management systems (LMS) have been frequently employed. Teachers are now required to use solutions developed since the epidemic, such as introducing blended learning with the use of an LMS, even in regular on-site classrooms. One of the learning management systems (LMSs) utilized by teachers and lecturers throughout the world is Canvas Instructure, a web-based and application-based LMS. This study looked into how students in a higher- education vocational setting perceived the use of Canvas Instructure as an extra learning platform in flipped ESP classes. To learn more about the usage of LMS in ESP classrooms, 108 students were given a questionnaire and semi-structured interviews. The study's conclusions show that students are generally in favor of using Canvas Instructure in flipped ESP classes. The vast majority of students agree that Canvas Instructure is user-friendly, helps them learn English more effectively, and makes it straightforward for them to access the course materials. Thus, using Canvas Instructure for other disciplines is highly recommended.